Infiltration Studies on the Soils of Chambal Command Area Kota, Rajasthan - Nathani, G.P.; Sharma, D.L.; Nagar, R.P. (Journal of Soil and Water Conservation, 2022)
The infiltration studies were carried out on the soils of four different soil series of Cham- bal Commanded Area. The rates of infiltration in dark brown or dark greyish brown clayey soils in Kota series is low to moderate and varying from 0.51 to 1.36 cm/hour with an exception of Arjunpura field where the rate was low due to the presence of a compact layer below 20 cm with high percentage of exchangeable sodium. Soils of Chambal series have very low to low intake rates. The infil- tration rate in this series varies from 0.15 cm. to 0.30 cm/hour inclay loam soils and 0.09/ hour in clayey soil. These soils took more than 8 hours for the absorption of 7 cm of water. The soils of Bundi and Sultanpur series belong to high intake family. Infiltration rate incase of Sultanpur series was 2.32 cm/hour. In the high intake family, the soils absorb 7 cm of water in about I to 1.5 hours. Very low to low intake rate of soils in Chambal and Kota series may be improved by deep ploughing or subsoiling operation and green manuring. Infiltration is the downward movements of water through the soil surface into the soil. Eagleson (1970) has defined infiltration rate as the rate at which water penetrates the ground surface at anytime under the combined forces of gravity, capillarity and viscosity. The movement of ground water in the soil takes place through the gravity channels and capillary pores under gravitational as well as capillary forces.